MYOPIC LOSS AVERSION DAN PERILAKU PENGAMBILAN KEPUTUSAN INVESTASI BERISIKO: STUDI EKSPERIMENTAL (Fokus Ekonomi, 2008)
This article tries to analyze the psychology bias that happen when an individual is taking a high risk investment decision. By referring on the Myopic Loss Aversion Theory (MLA), the subsequent is conducted by manipulation towards the participants through two kinds of treatment (frequent and infrequent), by using ‘within—subject’ design. The experiment result pointed showed that there is a consistency of the participants toward the MLA theory. Analysis from the gender side indicates that there is a significant of different behavior between male and female participants. Other finding also indicates that there is a ‘shock-effect’ which is experienced by the participants during the experiment. Suggestions for future research are provided. Key words: behavioral finance, myopic loss aversion, frequent and infrequent treatment, gender, and shock effect